Extreme Violence that Leads to Drain Iraqi Blood - Jabbar Frayyeh Shraida (Borong Newinera Publisher, 2022)
The current research aims at identifying the causes of Iraqi blood attrition from the point of view of Iraqis through a survey questionnaire presented by the researcher to 400 Iraqis. It was looking for mistakes within the Iraqi personality that contradicts the values of heaven, which increases the affliction day after day and continues in different forms. It results many reasons for the contradiction of values Heavenly is what makes the affliction continue. If we do not reconcile ourselves, we will not reconcile with God. It is known that reform begins with the self. The researcher found that the Iraqi personality differs from the personalities of other societies because it is linked to the personality of the household of the Messenger of God Muhammad, may God’s prayers and peace be upon him, as well as the prophets buried in the land of Iraq. It must follow the path of the prophets, the house of the Messenger of God, Muhammad and the family of Muhammad, and their morals, and to convey these morals to the whole world, and we will be the first society to export these morals without a competitor.